Cloning and expression of human vasohibin1 gene in E. coli - Malmir 1, Somaye; Mahmodabadi 1, Ali Zarei; Masoomikarimi 2, Masoomeh; Mirhoseini Ardakani 3, Soheilaalsadat; Roshaniasl 4, Elmira; Shekarforoush 3, Shahnaz; Jafarisani 5*, Moslem; Ahmadi 6, Reza (Shahroud Journal of Medical Sciences, 2016)
Background: Angiogenesis is an important process in various physiologic and pathologic states. The most significant stimulator of angiogenesis is vascular endothelial growth factor (VEGF). In contrast, vasohibin1 acts as an angiogenesis inhibitor which specifically inhibits new vessels formation. The aim of the present study was cloning and expression of vasohibin1 gene in E. coli as well as purification of recombinant vasohibin1 protein. Methods: Total RNA was extracted from human umbilical vein endothelial cells and cDNA was synthesized by RT-PCR. cDNA was amplified using a specific designed primer set. The PCR product was evaluated by electrophoresis and then cloned in pET28a expression vector which transformed into E.coli BL21 (DE3) as a host. IPTG is used as an expression inducer in media. Alternatively, PCR products were analyzed by sequencing and double digestion with EcoRI and HindIII restriction endonuclease. The expressed protein was purified by Ni-NTA column and confirmed by SDS Page and western blotting. Evaluation of gene inhibition was carried out through western blottting and RT-PCR. Results: No mutation or sequence variants were found in PCR products as a result of sequencing analysis. Moreover, the quantity and quality of expressed recombinant protein in the presence of IPTG with selected vector in E. coli was approximately high. VASH1 significantly prevented the receptor expression. The quality and level of expressed protein in pET28 expression vector indicated the efficacy of the applied system in vasohibin1 production. Conclusions: The produced vasohibin1 protein probably can be used as an angiogenesis inhibitor in further studies on retinopathies.